2015
DOI: 10.1002/hep.27492
|View full text |Cite
|
Sign up to set email alerts
|

Axl activates autocrine transforming growth factor‐β signaling in hepatocellular carcinoma

Abstract: Our data suggest that Axl/14-3-3ζ signaling is central for TGF-β-mediated HCC progression and a promising target for HCC therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
175
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(188 citation statements)
references
References 31 publications
12
175
1
Order By: Relevance
“…Increasing evidence has suggested that signaling pathways such as WNT/β-catenin and TGFβ/SMAD pathways may be involved in modulating tumorigenesis [33, 34]. Among these pathways, activation of TGFβ/SMAD plays an important role in enhancing the EMT to remodel the prometastasis phenotype [11], and SNAIL family members are regulated by the TGFβ/SMAD signaling pathway [22].…”
Section: Resultsmentioning
confidence: 99%
“…Increasing evidence has suggested that signaling pathways such as WNT/β-catenin and TGFβ/SMAD pathways may be involved in modulating tumorigenesis [33, 34]. Among these pathways, activation of TGFβ/SMAD plays an important role in enhancing the EMT to remodel the prometastasis phenotype [11], and SNAIL family members are regulated by the TGFβ/SMAD signaling pathway [22].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, AXL upregulation and activation by GAS6 has been implicated in the EMT of breast cancer and hepatocellular carcinoma (28,29). Likewise, the expression of both AXL and GAS6 is deemed to be closely related to full-blown EMT in a subset of lung AD.…”
Section: Univariate Analysis Multivariate Analysismentioning
confidence: 99%
“…Our recent data demonstrated that the siRNA-mediated loss of Axl expression caused a decrease of cell motility of human hepatoma cells (27). Therefore, we next analyzed the effects of the genomic editing events on the migratory cell behavior by performing a wound healing assay.…”
Section: Migration Of Crispr/cas9-edited Hepatoma Cellsmentioning
confidence: 99%
“…Chromosomal abnormalities occur in 75% of blood cancers and in more than 90% of solid tumors including hepatocellular carcinoma (HCC) (25,26). The overexpression of the receptor tyrosine kinase Axl along with the release of soluble Axl (sAxl) was detected in HCC and correlated with poor survival of HCC patients (27,28). In this study, we have generated knockouts of Axl in hepatoma cell lines using NHEJ-mediated CRISPR/Cas9 knockout technology.…”
Section: Introductionmentioning
confidence: 99%